Nectar trichome structure of aquatic bladderworts from the section Utricularia (Lentibulariaceae) with observation of flower visitors and pollinators - Płachno, Bartosz J.; Stpiczyńska, Małgorzata; Adamec, Lubomír; Miranda, Vitor Fernandes Oliveira [UNESP]; Świątek, Piotr (Springer Nature, 2018)
In Utricularia, the flower spur is a nectary and in this organ, nectar is produced and stored. This study aimed to examine the structure of the nectary trichomes in four Utricularia species (Utricularia vulgaris L., U. australis R.Br., U. bremii Heer and U. foliosa L.) from the generic section Utricularia. We have investigated whether species with different spur morphology had similar spur anatomy and nectary trichome structure. In Utricularia flowers, nectar is produced by spur capitate trichomes (sessile or stalked). Our results showed that regardless of the various spur morphology, trichomes have similar architecture and ultrastructure. Head cells of these trichomes are transfer cells with an eccrine nectar secretion. Examined species differed in the micromorphology of papillae in spurs. The fly Eristalis tenax was found to be a pollinator of U. vulgaris. Small Halictidae bees seem to be pollinators of U. foliosa.
Keywords: Bladderwort; Carnivorous plant; Entomophily; Floral micromorphology; Lentibulariaceae; Nectar; Nectary ultrastructure; Pollination; Sect. Utricularia; Spur; Trichomes